Individual motivation factors in agile teams - Philipp Arndt (Journal of Applied Leadership and Management, 2020)
Research questions: Do people in agile organizations experience a higher fulfillment of intrinsic motivational needs? Does the fulfillment of motivational needs depend on companies' agile maturity? Methods: By means of an online survey, a quantitative study with members of agile and traditional project teams was conducted and hypotheses were tested. The main target groups were project team members in industry in the German-speaking ("DACH") region. Results: The considered intrinsic motivation factors affiliation, acknowledgement, purpose, growth, autonomy, and performance were assigned a high importance by the participants. The agile maturity of companies, which is derived from the organizational elements strategy, structure, processes, leadership, and corporate culture, has a greater influence on the fulfillment of the motivationalneeds than the change from traditional project management to an agile project management method such as scrum. With an increase in agile maturity, the fulfillment of the six pre-defined individual motivational needs also increases.
Keywords: 650